Evaluation of Radiation and Radiation Protection Awareness Among Radiographers Working in Hospitals of Gilgit-Baltistan (GB), Pakistan - Raza, Muhammad; Hussain, Basharat (The Nucleus, 2025)
Radiation, in terms of ionizing or non-ionizing form, has always had a pivotal role in the field of medical diagnosis and treatment. Its uses also contain a lot of risk and increase the risk of cancer. Numerous challenges with radiation awareness, hazards, protections, safety measures, and dosimetry usage need to be evaluated in radiology departments of public and private hospitals located in Gilgit-Baltistan (GB). This study aims to assess the radiation protection awareness and practices among radiographers working in public and private hospitals of Gilgit-Baltistan (GB). This study included 18 public sectors and 21 private sector hospitals (total of 39) in GB. Mostly general radiography, computed tomography, and dental radiography are used in all hospitals included in this study, along with that some hospitals also using mammography, MRI, and interventional radiology. All hospitals included in this study have limited resources of radiation facilities. This Cross-sectional study was carried out using a validated questionnaire, which was completed by 74 (67 male & 7 female) radiographers. The data was collected through purposive sampling and analyzed using Statistical Package for Social Sciences (SPSS), version 21.0. This study concludes that 93.2 % of radiographers are well-aware that X-ray emits ionizing radiation, but only 36.5 %, and 32.4.0%, respectively, think that Ultrasound and MRI emit ionizing radiation. And 97.3 % of radiographers are aware of the radiation sensitivity of the Human Reproductive Organs.